Nitrogen balance and outcomes in critically ill patients: A systematic review and meta-analysis - Zhu, Yi-Bing; Yao, Yan; Xu, Yuan; Huang, Hui-Bin (Frontiers in Nutrition, 2022)
Abstract Objective: Nitrogen balance (NB) is a commonly used nutrition indicator in clinical practice, while its relation to the interpretation of protein malnutrition and outcomes in critically ill patients remains unclear. This study aimed to evaluate the impact of NB on prognosis in such a patient population. Methods: We searched for relevant studies in PubMed, EMBASE, and the Cochrane Database up to May 10, 2022. Meta-analyses were performed to evaluate the relationship between NB (initial, final, or absolute change of NB levels) and prognosis and important clinical outcomes in critically ill patients. Pooled odds ratios (ORs) and mean differences (MDs) together with their 95% confidence intervals (CIs) were calculated. We also conducted subgroup analyses to explore the sources of heterogeneity. Results: Eight studies with 1,409 patients were eligible. These studies were moderate to high quality. When pooled, the initial NB was comparable between the survival and non-survival groups (5 studies, MD 1.20, 95% CI, -0.70 to 3.11, I2=77%; P=0.22), while a significantly higher final NB in the survival group than that in the death group (2 studies, MD 3.69, 95% CI, 1.92 to 5.46, I2=55%; P<0.0001). Two studies provided the absolute change of NB over time and suggested survival patients had more NB increased (MD 4.16 g/day, 95% CI, 3.70 to 4.61, I2=0%; P<0.00001). Similarly, for studies utilizing multivariate logistic regression, we found an improved NB (4 studies, OR 0.85, 95% CI, 0.73-0.99, I2=61%; P=0.04) but not an initial NB (2 studies, OR 0.92, 95% CI 0.78-1.08, I2=55%; P=0.31) was significantly associated the risk of all-cause mortality. These results were further confirmed in subgroup analyses. In addition, patients with improved NB had more protein and calorie intake and a similar length of stay in hospital than those without. Conclusions: Our results suggested that an improved NB but not the initial NB level was associated with all-cause mortality in critically ill patients. This highlights the requirement of dynamic monitoring NB during nutrition treatment. Further randomized clinical trials examining the impact of NB-guided protein intake on clinical outcomes in critically ill patients are warranted.